Attribution and Health Seeking Behavior of Family Members towards Conversion (Dissociative) Disorders - Rizwan Farooq, Unaiza Jawad, Muntazir Mehdi, Madiha Malik, Adil Umer Khan, Shafqat Huma, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Patients with conversion disorder (dissociative disorder) are common in various hospitals and communities in Pakistan. What people think about the disease decides what treatment they receive. Therefore, this analysis was held to determine the attribution and health seeking behaviours for conversion disorder. Study Design: A cross-sectional and exploratory hospital study. Place and Duration: In the department of Psychiatry and Behavioral Sciences PGMI /AMC / LGH, Lahore Pakistan for the duration from February 2022 to July 2022. Methods: A total of 60 patients were included in this study and selected with purposive sampling method. Conferring to the criteria of ICD 10; the analysis of dissociative disorder was made. A self-developed questionnaire was used. The help seeking behavior and knowledge regarding dissociative disorder was assessed by self developed questionnaire. Results: The results exhibited that the frequency of dissociative convulsions (26.8%) and possession and trance (33.3%) were higher than in the other groups. Similarly, 8 (13.3%) had stupor, 6 (10%) has motor disorders in all movement and (3.3%) has sensory disorders and (5%) had mixed dissociative disorder. It was found that the majority of family members seeking treatment from faith healer (63.3%), trailed by paramedics (11.7%) and doctors (25%). Of all subjects, 46.6% visited a mental health professional for more than 2 weeks, 31.7% visited them within 48 hrs to two weeks, and 21.7% within 48 hours. 38.3% of members answered to ailment as a physical cause. About 43.3% of participants said conversion disorder was a mental condition. The participants who replied disease as a supernatural problem were 40%. Solitary 35% of contributors believed that counseling, psychotherapy and medicine could cure conversion disorder, while 46.7% believed that a faith-healer might cure it. Conclusion: Societies in Pakistan still have their roots in ethnic practices and faith healing. It is very important to run the awareness program and work in co-operation with faith healers is significant. Keywords: Conversion (Dissociative) Disorder, Attribution, health seeking, attribution